The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.18569/tempus.v10i1.1859
|View full text |Cite
|
Sign up to set email alerts
|

Saúde ocupacional e riscos psicossociais em trabalhadores da limpeza de instituição de ensino superior: Um estudo qualitativo em Brasília, DF.

Abstract: O objetivo deste estudo foi analisar a percepção dos funcionários da limpeza em uma instituição pública de ensino superior sobre condições de trabalho e saúde no meio universitário, comênfase para os aspectos físico-ambientais e psicossociais que determinam a saúde deste grupo no ambiente onde estão inseridos. Foi conduzida uma pesquisa qualitativa, utilizando-se a técnica de entrevista em profundidade junto a 16 funcionários da limpeza de ambos os sexos. Os trabalhadores têm a percepção de que não são devidam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
5
0
5
Order By: Relevance
“…There was also a significant correlation between hearing impairment and common mental disorders. This prevalence was high compared to another study that associates hearing disorders with the psychic suffering caused by isolation, constraints and frustrations, in addition to the people reporting fatigue due to the mental effort in the communication process (4) . Hearing impairment and dizziness, which also had a significant correlation with common mental disorders, may be associated with multiple factors involving the labyrinth and the vestibular apparatus, such as medications, internal conditions, genetic factors and women in the menopause, but there is evidence that anxiety and stress contribute to the appearance of these symptoms that are more common among women and contribute to promote muscle pain due to the contractures to maintain balance (17) .…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…There was also a significant correlation between hearing impairment and common mental disorders. This prevalence was high compared to another study that associates hearing disorders with the psychic suffering caused by isolation, constraints and frustrations, in addition to the people reporting fatigue due to the mental effort in the communication process (4) . Hearing impairment and dizziness, which also had a significant correlation with common mental disorders, may be associated with multiple factors involving the labyrinth and the vestibular apparatus, such as medications, internal conditions, genetic factors and women in the menopause, but there is evidence that anxiety and stress contribute to the appearance of these symptoms that are more common among women and contribute to promote muscle pain due to the contractures to maintain balance (17) .…”
Section: Discussionmentioning
confidence: 63%
“…Satisfaction is a subjective, intimate emotion, related to a pleasurable feeling, marked by previous experiences, expectations, values that can be linked to both organizational and physical factors as well as interpersonal relationships, going beyond the simple definition of work itself (3)(4)7) . The dissatisfaction is linked to negative feelings, poor recognition, conflicts between bosses and colleagues and low salaries, which can contribute to mental illness and worsen quality of life (1,(3)(4)7,18) . A review of the literature indicates dissatisfaction as a source of damage to physical, mental and social health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A broad approach with the aim of identifying biological, psychological, social and organizational aspects is needed to gain a better understanding of the profile of these workers. Some studies in Brazil have investigated the profile, organizational aspects, working conditions [4,[22][23][24], work ability [25][26][27] and musculoskeletal symptoms [6,9] in cleaners. However, this population is largely overlooked and there is a lack of knowledge regarding their working and health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of risk factors for illness has been the objective of research with samples from different professional categories, as it is the case of teachers (García et al, 2016), in which the risks are characterized by high psychological demands, low self-esteem, scarce social support and job insecurity. General service workers working in the health sector (Andrade et al, 2016), showed muscle pain, exhaustion and stress, associated with the lack of support from management. In the area of health, the risk of illness for nurses was the pace of work (97.6%), insecurity about working conditions (66.1%), as well as high emotional demands (65, 2%) (Jimenez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%